Treasury Single Account : Concept, Design and Implementation Issues - Fainboim Yaker, Israel; Pattanayak, Sailendra (Washington, D.C. : International Monetary Fund, 2010)
A treasury single account (TSA) is an essential tool for consolidating and managing governments' cash resources, thus minimizing borrowing costs. In countries with fragmented government banking arrangements, the establishment of a TSA should receive priority in the public financial management reform agenda. Drawing on the lessons of the Fund's work in several countries in establishing a TSA, this paper explains its concept, essential features, and potential benefits. It also presents alternative models and approaches for designing a TSA that take into account specific country contexts as well as the preconditions and desirable sequencing for its successful implementation. Finally, the paper includes country examples from different regions in support of the analysis and recommendations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet